2018
DOI: 10.3389/fphys.2018.01745
|View full text |Cite
|
Sign up to set email alerts
|

Disrupt of Intra-Limb APA Pattern in Parkinsonian Patients Performing Index-Finger Flexion

Abstract: Voluntary movements induce postural perturbations which are counteracted by anticipatory postural adjustments (APAs). These actions are known to build up long fixation chains toward available support points (inter-limb APAs), so as to grant whole body equilibrium. Moreover, recent studies highlighted that APAs also build-up short fixation chains, within the same limb where a distal segment is moved (intra-limb APAs), aimed at stabilizing the proximal segments. The neural structures generating intra-limb APAs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This aspect agreed with the general view that assigns to the cerebellum the role of a "timing-machine" [41][42][43][44][45] and leaves the pattern selection to other brain structures, like the basal ganglia. Such a perspective has been confirmed also for what regards APAs in adults [46,47].…”
Section: Discussionsupporting
confidence: 53%
“…This aspect agreed with the general view that assigns to the cerebellum the role of a "timing-machine" [41][42][43][44][45] and leaves the pattern selection to other brain structures, like the basal ganglia. Such a perspective has been confirmed also for what regards APAs in adults [46,47].…”
Section: Discussionsupporting
confidence: 53%
“…The present study belongs to a broad line of research oriented to investigate how the APA control is organized. In fact, several studies showed the role of sensory and motor areas, including the primary and supplementary motor cortices, as well as subcortical structures like basal ganglia, cerebellum and spinal cord (Viallet et al, 1992; Palmer et al, 1994; Petersen et al, 2009; Bolzoni et al, 2012, 2015, 2018; Ng et al, 2013; Bruttini et al, 2015). Although it is still not well established whether the command for recruiting the prime mover muscles and that governing the postural muscles are separately processed or have a common origin, we provided evidence that a functionally unique motor command should drive both the prime mover and the muscles of the intra-limb APAs chain (Bruttini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Schmitz et al (2005) [56] reported the involvement of Sensorimotor Areas, using functional Magnetic Resonance Imaging, while Schepens et al (2004) [57] reported that the Pontomedullary Reticular Formation, a site of integration of signals from both cortical and subcortical structures, is able to mediate APAs in time and magnitude, to optimize motor control of posture and movement in the cat. Moreover, basal ganglia have been reported to contribute to APA control (Figure 1); in particular, a disruption in intra-limb APAs associated with the index finger flexion [58] and an impairment in inter-limb APAs during a bimanual load-lifting task [59] have been found in patients with Parkinson's disease. Cortices, as well as about the motor goal from SMA and Premotor Cortices.…”
Section: Overview Of Anticipatory Postural Adjustmentsmentioning
confidence: 99%
“…Therefore, this work supports the hypothesis that the cerebellum plays a key role also during human development, in particular, in building up internal models of gait initiation timings. Moreover, considering that the APA pattern was not affected by cerebellar dysfunction, pattern selection is a functional skill which may be attributed to other brain structures, like the basal ganglia [58].…”
Section: Role Of Cerebellum In the Ontogenesis Of Apa Controlmentioning
confidence: 99%